P627 Stopping anti-tumour necrosis factor (TNF) therapy in patients with perianal Crohn's disease: Results from a population-based study. (25th January 2019) - Mak, W Y; Tang, W; Chan, F K L; Leung, W K; Li, M K K; Lo, F H; Ng, C K M; Sze, A S F; Leung, C M; Tsang, S W C; Shan, E H S; Chan, K H; et al.
Abstract: Background: Little is known of the outcome of patients with perianal Crohn's disease (PCD) after stopping anti-TNF. Aim: To assess rate of relapse in PCD patients after stopping anti-TNF. Methods: Consecutive PCD patients treated with anti-TNF therapies were identified from a territory wide Hong Kong IBD registry which covers 13 public hospitals in Hong Kong. Patients' disease characteristics, drug therapies and clinical outcomes were retrospectively reviewed from medical records and analysed. Results: Sixty-three PCD patients received anti-TNF from 1997 to 2016. Median age at PCD diagnosis was 24 years (interquartile range, IQR: 20–28) and 72% were male. Median follow-up was 10 years (IQR: 6.3–14.5 years). Fifty-nine patients had complex fistulas. All had thiopurines in addition to anti-TNF. Twenty-seven patients (42.9%) achieved clinical remission, defined as complete cessation of fistula drainage, after median of 6 months (IQR: 4–10 months). Ten (15.9%) achieved radiological healing, defined as complete resolution of previous high signal tract or subtle, narrow calibre intermediate signal tract. Radiological healing lagged behind clinical healing by median of 7 months (IQR, 3–10 months). Thirty-eight patients (60%) stopped anti-TNF after median duration of 13 months (IQR: 4–24 months). Reasons for stopping included: financial reason ( n = 11), loss of response ( n = 10), achieving clinical remission ( n = 9), side effects (including two tuberculosis) ( n = 6) and patient's choice ( n = 2). Twenty-one patients (55.2%) developed PCD relapse, defined as increased fistula drainage or recurrence of previously healed fistula, after stopping anti-TNF. Of which, 5 had relapse of both PCD and luminal Crohn's disease. Four had relapses of luminal CD alone. Median time to PCD relapse was 8 months (IQR: 3–14 months). Cumulative probabilities of PCD relapse were 46.5% at 12 months, 58.2% at 24 months and 71.1% at 36 months respectively. Seven out of 13 (53.8%) PCD patients with clinical remission relapsed after stopping anti-TNF. None of the PCD patients with radiologically healed fistula relapse after stopping anti-TNF. Among those who developed PCD relapse, 8 (38%) required defunctioning surgery and one required proctectomy. Twenty-seven switched to thiopurines, 6 to methotrexate, one to thalidomide and one to tacrolimus after stopping anti-TNF. Twenty-five patients (92.6%) restarted biologics (one vedolizumab, 24 anti-TNF) and 20 (80%) regained response. Conclusions: More than half of PCD patients developed relapse after stopping anti-TNF. Majority regained response after restarting anti-TNF. Larger and longer-term studies are needed to investigate the role of deep fistula healing and de-escalating therapy in PCD.